Estrategias didácticas y su influencia en el aprendizaje autónomo en los niños de educación inicial de la Unidad Educativa Francisco Huerta Rendón - Icaza Díaz, Karina Marisela (2023)
The purpose of carrying out this research is to determine the importance of didactic strategies and how they influence the autonomous learning of children, analyzing the contribution they provide in the teaching-learning process, identifying how they benefit and in turn describing the strategies that influence in this process. The use of didactic strategies favors the teaching-learning process, becoming a primary instrument for both teachers and students, its use in the classroom being essential to achieve meaningful learning, with the purpose of enabling children to develop their skills and skills, the use of these strategies provide help to teachers in their teaching process with a series of methodological guidelines that will facilitate the implementation and application of activities in a clear way, guiding them in the process of guiding learning. It is essential that teachers make use of strategies to promote autonomous learning since through the application of activities they allow their students to have an active interaction, get involved individually and in groups, encouraging them to want to participate, developing in them a thought critical, improving their skills and abilities, developing intellectually and emotionally, turning each of the children into active entities in their training process, in this way they will have the ability to face everyday situations and function in activities appropriate to their age.